PENGARUH KESELAMATAN DAN KESEHATAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. XYZ - -, RIAN HIDAYAT (Jurnal TIN Universitas Tanjungpura, 2017)
PT.XYZ is a company engaged in the production of palm oil and kernels are located in the village of Sui. Enau, District Tebas, Sambas, West Borneo. The Company has implemented a program of occupational safety and health in the work area so that the risk of accidents can be avoided. The problem faced by companies is still high number of accidents that happen to employees based on reports of accidents and diseases in the month of January until August 2015 as many as 6.6%, which occurred in 93.4% of occupational accidents and illnesses experienced by the employee at the time of work activities so that it can affect the performance of employees at the company. The purpose of this research is to know the effect of occupational safety and health on the performance of employees of PT. XYZ.The method used in this research is the method of Partial Least Squares (PLS) with the help of software Smartpls 3.0. Partial Least Squares (PLS) is a method alternetif of Structural Equation Modeling (SEM) were used to determine how much influence the independent variable on the dependent variable. The steps performed in the method of PLS, namely: designing the structural model, designing measurement models, prepare the construction of the path diagram, conversion path diagram into the equation, estimation of the path coefficients (parameters), evaluation Goodness of fit, and hypothesis testing.The results of T-test analysis using the statistical method of PLS shows that safety does not significantly influence employee performance with a value of statistic t <t table is 1.567 <1.96. While occupational health significantly influence employee performance with a value of statistic t> t table is 7.295> 1.96. Based on the test results on the path coefficient value PLS method, for safety variables (X1) on employee performance (Y) is -0.124, meaning that there are significant safety negatively affect the performance of the employee, while the influence of occupational health (X2) on employee performance (Y) amounted to 0.594, meaning that the occupational health positive influence on employee performance. Increasingly improved occupational health of the employees at the company, the higher the performance of employees. Recommendations can be given to improve the performance of employees at PT. XYZ which companies provide personal protective equipment according to prevailing standards, in order to obtain comfort in use. Health programs that have applied the company maintained and further improved employee productivity in order to become more optimal.Keyword: palm oil, occupational Safety, occupational health, Partial Least Squares (PLS)